1992
DOI: 10.1159/000138991
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Pyrazinoyl-guanidine, 3-Aminopyrazinoyl-guanidine and Their Corresponding Pyrazinoic Acid Metabolites in Humans and Dogs

Abstract: Pyrazinoylguanidine (PZG), 3-aminopyrazinoylguanidine (NH2PZG) and their pyrazinoic acid metabolites were measured by a new reverse-phase HPLC method in the serum of dogs and humans after administration of PZG, NH2PZG or 2-pyrazinoic acid (PZA). Kinetic properties of PZG and its principal metabolite, PZA, were studied in normal humans and also in azotemic patients, since PZG acts on renal tubules of patients with kidney failure to increase urea elimination. In humans and dogs, PZG was rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The doses of PZG (900 mg) and PZA (300 mg) were selected to give comparable blood concentrations based on our previous pharmacokinetic studies [1].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The doses of PZG (900 mg) and PZA (300 mg) were selected to give comparable blood concentrations based on our previous pharmacokinetic studies [1].…”
Section: Methodsmentioning
confidence: 99%
“…Pyrazinoylguanidine (PZG), a novel drug structurally related to amiloride, is rapidly hydrolyzed by esterases in human serum to pyrazinoic acid (PZA) [1]. Pharmacokinetic studies in normal human subjects revealed serum half-lives of 1.1 h for PZG and 3.3 h for PZA [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…STZ-diabetic rats differ in some respects from both NIDDM and insulin-dependent diabetes mellitus, but resemble the latter more than the former [12], The current stud ies had the following objectives: (a) to deter mine whether PZG, glyburide, and metfor min can ameliorate the metabolic abnormali ties of elevated plasma glucose and lipid con centrations in STZ-diabetic rats; (b) to deter mine whether PZG's metabolic effects in STZ-diabetic rats are mediated in part by pyrazinoic acid (PZA), a metabolite of PZG [13]; and (c)to determine whether 3-amino-PZG, a structural analog of PZG [6,7,13], and its hydrolytic product, 3-amino-PZA [6,7,13], can reduce elevated plasma glucose and lipid concentrations that occur in the STZ-diabetic rat model.…”
Section: Introductionmentioning
confidence: 99%